ОБЗОР МЕТОДОВ ПОЛУЧЕНИЯ КОСМИЧЕСКИХ ИЗОБРАЖЕНИЙ С ВЫСОКИМ РАЗРЕШЕНИЕМ - Сеитназаров, К.К.; Турдышов, Д.Х.; Туремуратова, Б.К.; Мухиятдинов, Н.С. (SCIENCE and SOCIETY, 2023)
This article provides an overview of obtaining high-quality satellite images can be method, and also provides brief information about geosynchronous equatorial and low Earth orbits. Further more the article discusses the highest and lowest resolutions of satellite images, as well as which companies provide these images. The comparison of aerial photographs is given obtained with the help of unmanned vehicles and satellite images. It also provides information about the future plans of companies that are engaged in providing satellite images.